Influence of organic fertilizer in the production and economic efficiency of Brachiaria Humidicola - Loi, Bui Van; Ty, Nguyen (Edelweiss Applied Science and Technology, 2025)
Hairless grass (Brachiaria humidicola) grown in Thua Thien Hue initially showed that it can adapt to the weather and climate conditions in Thua Thien Hue. The study aimed to evaluate this grass species’ growth capacity, production capacity, and economic efficiency when using different levels of organic fertilization. The experiment was conducted on four fertilization regimes of 10, 20, 30, and 50 tons of organic fertilizer per hectare in a 1-year cycle; for each hectare, we chose 5 points for data collection and analysis of nutritional values and measurement of productivity. The results showed that increasing the amount of fertilizer enhanced the green growth capacity, the yield of each hectare, and the economic efficiency of Brachiaria humidicola (P < 0.05). Increasing the amount of organic fertilizer to 50 tons per hectare did not differ from 30 tons per hectare. A fertilization regime of 30 tons per hectare for grass has brought high economic efficiency in livestock farming of goats and cattle. Additionally, green matter, dry matter, and protein yield were above 12.89, 3.62, and 0.98 tons per hectare per time harvested. Furthermore, this result also showed that dry matter (%), crude protein, total minerals, and insoluble fiber in the neutral detergent of B. humidicola were 25.36, 7.92, 70.87, and 8.73% dry matter, respectively. Our research results could provide more useful information about the newly introduced grass of B. humidicola planted in rice croplands. This might benefit local farmers in converting cultivated crops from growing rice to grasses for cattle. Our data will provide scientific data and experimental facilities for planting new species for climate change adaptation in Thua Thien Hue province areas.